High-pressure and high-temperature phase relations of an orthopyroxene granulite from McIntyre Island, Enderby Land, East Antarctica - Kawasaki, Toshisuke; Motoyoshi, Yoichi (National Institute of Polar Research, 2000)
P(論文) High pressure experiments have been carried out from 9 to 20 kbar and 900 to 1300°C by the aid of a piston cylinder apparatus to simulate the equilibrium conditions of an orthopyroxene granuhte from Mclntyre Island, Enderby Land, East Antarctica The following two assemblages have been obtained with increasing pressure at a constant temperature orthopyroxene + quartz and garnet + orthopyroxene + quartz The boundary curve between these two assamblages has been approximated as the following linear equation p (kbar) = 001287T (℃)-0 27 Garnet is unstable and disappears at the low pressure side of this curve The Fe-Mg distribution coefficients between orthopyroxene and garnet, KD [=(X^<Grt>_<Fe>X^ _<Mg>)/(X^<Grt>_<Mg>X^ _<Fe>)], were experimentally determined at these P-T conditions, showing that the logarithm of K_D can be approximately expressed by a linear function of the reciprocal of the absolute temperature lnK_D=-1 49 + 2815/T (K) Combining the petrographic data and the experimental data, we can infer this granulite experienced retrograde metamorphism at 112 kbar and 895℃ and subsequently passed at a certain pressure between 10 9 kbar and 11 4 kbar at 873℃ departmental bulletin paper